\(2x\left(x-3\right)+5\left(3-x\right)=0\)
\(\Leftrightarrow2x\left(x-3\right)-5\left(x-3\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left(2x-5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=\dfrac{5}{2}\end{matrix}\right.\)
\(\text{2x( x-3 ) + 5( 3 - x )= 0 }\)
\(\Leftrightarrow2x^2-11x+15=0\)
\(\Leftrightarrow\left[{}\begin{matrix}2x-5=0\\x-3=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{5}{2}\\x=3\end{matrix}\right.\)
\(2x\left(x-3\right)+5\left(3-x\right)=0\)
\(\Leftrightarrow2x\left(x-3\right)-5\left(x-3\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left(2x-5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-3=0\\2x-5=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=\dfrac{5}{2}\end{matrix}\right.\)